Association of RTN4 indel polymorphisms with the risk of tumorigenesis in the Chinese Han population: RTN4 polymorphisms and tumorigenesis risk - Ou, Xun; Peng, Shengjie; Han, Xiaoyu; Zhou, Surui; Fan, Lu; Gao, Xueren (Cellular and Molecular Biology, 2023)
Although studies have reported the association of two insertion/deletion (indel) polymorphisms in the 3’-untranslated region (UTR) of the RTN4 gene with the risk of tumorigenesis, the findings are inconsistent and require further explanation. Comprehensive literature searches were undertaken in Pubmed, Embase, Web of Science, China National Knowledge Infrastructure, and WangFang database. The risk of tumorigenesis was determined using odds ratios (ORs) and 95% confidence intervals (CIs) based on STATA 12.0 software. A total of four case-control studies with 1214 patients and 1850 controls focused on the RTN4 gene TATC/- polymorphism and five case-control studies with 1625 patients and 2321 controls on the RTN4 gene CAA/- polymorphism. Pooled analysis showed that the TATC/- polymorphism was not associated with the risk of tumorigenesis under all genetic models and the CAA/- polymorphism was significantly associated with the risk of tumorigenesis under the homozygote genetic model (Del/Del vs. Ins/Ins: OR=1.32, 95%CI=1.04-1.68, P=0.02). In conclusion, the current findings suggested that the CAA/- polymorphism in the 3’-UTR of the RTN4 gene was significantly associated with the risk of tumorigenesis in the Chinese population and may serve as a valuable marker for predicting tumor risk.